Correlation between Trochlear Dysplasia and Anterior Cruciate Ligament Injury. (August 2013) - Botchu, Rajesh; Obaid, Haron; Rennie, WJ
Purpose: To evaluate the correlation between trochlear dysplasia and anterior cruciate ligament (ACL) injury Methods: Magnetic resonance images (MRIs) of 95 knees in 54 males and 36 females aged 4 to 74 (mean, 28) years who had anterior knee pain and suspected ligamentous injury were reviewed. The MRIs were independently reviewed by 2 musculoskeletal radiologists on 2 occasions. According to the Dejour classification, trochlear dysplasia was classified into types A, B, C, and D. Intra-articular injuries/disorders of the patients included patellofemoral osteoarthritis, chondromalacia patella, meniscal tears, and ligamentous injuries. Intra- and inter-observer variability was calculated. Results: 58 of the knees had trochlear dysplasia, 38 of which were Dejour type A. The intra- and inter-observer variability was good to excellent (Kappa=0.76–1). ACL tear was the most common injury (n=13). No ACL injury occurred in patients without trochlear dysplasia. The odds of having sustained an ACL injury were 8.8 fold greater in Dejour type-A knees than in non–type-A knees (p=0.023). Conclusion: Dejour type-A trochlear dysplasia was associated with ACL injuries.